Implications of climate change for shipping: Opening the Arctic seas. (8th February 2018) - Ng, Adolf K.Y.; Andrews, Jonathan; Babb, David; Lin, Yufeng; Becker, Austin
Abstract : This paper assesses the value and environmental feasibility of Arctic shipping by reviewing the relevant scientific and economic peer‐reviewed literature. From the physical perspective, this paper examines the impact of climate change on sea ice and marine weather and considers the resultant consequences for Arctic shipping accessibility. From an economic perspective, it reviews the major research investigating the economic feasibility of diverting ships from conventional shipping routes to Arctic routes, the attitudes of shipping stakeholders, and other major factors affecting the prospect of Arctic shipping. This review also identifies important research gaps. Ultimately, we find that the complex environmental and economic dynamics of the Arctic suggest that an appropriate understanding of Arctic shipping will require close collaboration between natural and social scientists. This article is categorized under: Assessing Impacts of Climate Change > Evaluating Future Impacts of Climate Change Abstract : The 1981–2010 average maximum (March) and minimum (September) sea ice extent and the three northern major shipping routes (and regions): the Northwest Passage (NWP), the Northern Sea Route (NSR), and the Trans‐polar Sea Route (TSR).